The Effect of E-service Quality and Customer Satisfaction and Trust to Customer Online Shopping Behavior - Song, Liying (International Journal of Global Economics and Management, 2024)
China's e-commerce sector is experiencing rapid growth. Among Chinese cities, Beijing stands out with its robust development, consistently ranking among the top three in the nation. Nonetheless, Beijing's e-commerce enterprises encounter various challenges. This research endeavors to examine the interplay between e-service quality, customer satisfaction, trust, and online shopping behavior within the Beijing e-commerce landscape. Descriptive method was considered by the researchers. The respondents of the study are the users of online shopping platforms that operates in Beijing China who have experience using major online consumption platforms. The sample size is 385 people which was calculated by Raosoft software. The respondents of the study were chosen using the simple random sampling design. Moreover, constructed survey questionnaires served as a tool with five-key point Likert scale. The Statistical Package for Social Sciences (SPSS) was employed in the statistical analysis of data. The following statistical tools were used in the study: frequency and percentage, mean, reliability and validity analysis, Analysis of Variance and Multiple Linear Regression. The study resulted in a strong positive relationship between customer satisfaction, trust and over-all e-service quality. Specifically, customer satisfaction and trust resulted in a very strong relationship to customer behaviors. For the comparison of means when grouped according to profile variables, customer satisfaction level and over-all e-service quality have a significant difference when grouped to frequency of purchase. Based on the results of the study, the researchers proposed a development program to help improve the quality of e-services and thus increase customer re-purchase rates.